Extent and Sources of Anxiety among Employees Attending a University Hospital Clinic - Othman, Zahiruddin; Yahya, Fariza (Japan International Cultural Exchange Foundation, 2018)
Objective: To study the extent and sources of anxiety among employees of Universiti Sains Malaysia. Methods: This was a cross-sectional study over a period of 4 months. A total of 300 employees of Universiti Sains Malaysia attending the staff clinic was recruited and given self-administered questionnaires including the Hospital Anxiety and Depression scale (HADS), Job Stress Scale and Life Event Scale to assess anxiety, job stress and life events, respectively. Result: The prevalence of anxiety among employees attending the staff clinic were 14.3% overall, 18.5% for males and 10.4% for females. Using multiple logistic regression, 4 independent variables were noted which include number of children, LCU score, relationship with supervisor and gender. Conclusion: The prevalence of anxiety among employees attending the staff clinic was comparable to other similar studies. The strongest predictor of anxiety in this study was poor relationship with superior with OR 9.58. This was followed by life events (i.e., high LCU scores) with OR 6.52 and number of children 5 or more with OR 3.40.